Etiopathogenetic mechanisms of epilepsy and comparative characteristics of audiogenic epilepsy experimental models - Е. D. Bazhanova; А. А. Kozlov; Yu. О. Sokolova (Эпилепсия и пароксизмальные состояния)
Epilepsy is a widespread neurological chronic disease characterized by recurrent seizures, manifested as short-term partial or generalized convulsions and accompanied by loss of consciousness. To correctly select a treatment method for epilepsy, it is necessary to investigate the cues resulting in its development, but it is not always possible to identify a cause of the disease and chose proper treatment. Drug resistance remains one of the major issues in treatment of epilepsy, despite a great body of studies describing its nature. In this regard, it is necessary to select a model for examining epileptic seizures and underlying mechanisms, searching for genes involved in regulation of epilepsy as well as assessing effectiveness and safety of new antiepileptic drugs. It was noted that rodents, especially Krushinsky–Molodkina rat strain represent a suitable genetic model for audiogenic epilepsy to dissect the mechanisms of epileptogenesis, genetic basis of seizure susceptibility, development of drug resistance, and testing new antiepileptic drugs. Despite that the audiogenic form of reflex epilepsy is quite rare in humans, it was revealed that the same underlying genes, molecular mechanisms and signaling pathways are responsible for enabling audiogenic seizures in rodents and human epilepsy, additionally coupled to developing similar neuroanatomical anomalies.